Application of Green Technologies in Design-Based Extraction of Celastrus paniculatus (Jyotishmati) Seeds, SEM, GC-MS Analysis, and Evaluation for Memory Enhancing Potential - Arya, Ashwani; Kaushik, Deepak; Almeer, Rafa; Bungau, Simona G.; Sayed, Amany A.; Abdel-Daim, Mohamed M.; Bhatia, Saurabh; Mittal, Vineet (Frontiers in Nutrition, 2022)
Background: The Celastrus paniculatus (CP), commonly known as Jyotishmati, is considered as ‘elixir of life’ by Indian people for the prevention/management of many ailments. The seed powder and its extract have widely used commercially for preparation of various Ayurvedic formulations for the improvement of memory. CP seeds were generally extracted by conventional extraction methods (CEM) which are assumed to impact environment burden and also produce low extract yield. Green extraction with possible improvement in extract yield has always been the need of hour for selected medicinal plant. Objective: In the present research, we aimed to optimize the different extraction factors in microwave and ultrasound based extraction. The various extracts obtained in conventional and green methods are also evaluated for the possible improvement in memory enhancing potential. Materials and methods: The selected medicinal herb was extracted by CEM (maceration and percolation). In green methods like microwave based extraction (MBE) and Ultrasound based extraction (UBE) various parameters were optimized using box-behnken design coupled with response surface methodology. The SEM and GC-MS analysis was also done to confirm the possible improvement in concentration of plant actives. The swiss albino mice were used to evaluate memory enhancing potential of different extracts. Results: At the optimized conditions MBE and UBE the extraction yield, TPC and TFC are significantly improved. The GC-MS analysis further confirms the improvement in concentration of certain fatty acid esters, pilocarpine and steroidal compounds in optimized extracts. The optimized extracts also exhibited the significant improvement in behavioural parameters, oxidative stress induced parameters and acetylcholinesterase inhibitory potential. Discussion and conclusion: From the results, we can say that the application of green technologies in design based extraction of selected herb not only significantly reduce the extraction time but also improves the extract yield and concentration of plant actives. In nutshell, it can be concluded that the green approaches for extraction of seeds of Celastrus paniculatus could be scale up at commercial level to meet the rising demand of herbal extract.